Application of bioelectrical impedance analysis in prediction of light kid carcass and muscle chemical composition. (17th October 2017) - Silva, S. R.; Afonso, J.; Monteiro, A.; Morais, R.; Cabo, A.; Batista, A. C.; Guedes, C. M.; Teixeira, A.
Abstract : Carcass data were collected from 24 kids (average live weight of 12.5±5.5 kg; range 4.5 to 22.4 kg) of Jarmelista Portuguese native breed, to evaluate bioelectrical impedance analysis (BIA) as a technique for prediction of light kid carcass and muscle chemical composition. Resistance (Rs, Ω) and reactance (Xc, Ω), were measured in the cold carcasses with a single frequency bioelectrical impedance analyzer and, together with impedance ( Z, Ω), two electrical volume measurements (VolA and VolB, cm 2 /Ω), carcass cold weight (CCW), carcass compactness and several carcass linear measurements were fitted as independent variables to predict carcass composition by stepwise regression analysis. The amount of variation explained by VolA and VolB only reached a significant level ( P <0.01 and P <0.05, respectively) for muscle weight, moisture, protein and fat-free soft tissue content, even so with low accuracy, with VolA providing the best results (0.326⩽ R 2 ⩽0.366). Quite differently, individual BIA parameters (Rs, Xc and Z ) explained a very large amount of variation in dissectible carcass fat weight (0.814⩽ R 2 ⩽0.862; P <0.01). These individual BIA parameters also explained a large amount of variation in subcutaneous and intermuscular fat weights (respectively 0.749⩽ R 2 ⩽0.793 and 0.718⩽ R 2 ⩽0.760; P <0.01), and in muscle chemical fat weight (0.663⩽ R 2 ⩽0.684; P <0.01). Still significant but much lower was the variation in muscle, moisture, protein and fat-free soft tissue weights (0.344⩽ R 2 ⩽0.393; P <0.01) explained by BIA parameters. Still, the best models for estimation of muscle, moisture, protein and fat-free soft tissue weights included Rs in addition to CCW, and accounted for 97.1% to 99.8% ( P <0.01) of the variation observed, with CCW by itself accounting for 97.0% to 99.6% ( P <0.01) of that variation. Resistance was the only independent variable selected for the best model predicting subcutaneous fat weight. It was also selected for the best models predicting carcass fat weight (combined with carcass length, CL; R 2 =0.943; P <0.01) and intermuscular fat weight (combined with CCW; R 2 =0.945; P <0.01). The best model predicting muscle chemical fat weight combined CCW and Z, explaining 85.6% ( P <0.01) of the variation observed. These results indicate BIA as a useful tool for prediction of light kids' carcass composition.